Proposal of marketing strategies for the airline Easyfly (2016)
The Colombian society doesn’t understand the meaning of low-cost airlines nor in front of the commercial and large airlines that have the domestic market. Those ones that do offer moderate services, it is evident in their tickets sell. In Colombia, it is possible to find different airlines that offer their services to travel anywhere. That’s the reason why travelers choose to travel by plane for reasons such as: business, leisure, and holiday’s seasons, among others. Indeed, people usually hesitate when they are about to travel with an airline. However, alliances and the presence of new airlines that offer flights abroad have directly affected the market by decreasing the use of the service. This is the main reason behind the making of this project. My proposal of marketing strategies to the low cost airline Easyfly will hopefully help them to join the domestic market and become recognized by the Colombian population to be used for travel. Also, this project proposes strategies to improve the airline’s image and to be highly recognized so it will be chosen as the first and preferred option by customers. Finally, get increase revenue for the airline.